Obtención y caracterización de la inulina a partir de dos variedades de agave cabuya negra (Agave americana l.) y agave sisal (Agave sisalana p.) con tres concentraciones de alcohol (40, 60, 80%) en los laboratorios académicos de la carrera de ingeniería agroindustrial de la Universidad Técnica de Cotopaxi en el período 2015-2016 - Molina Chasiquiza, Lorena Soledad (2016)
The research was made at the Technical University of Cotopaxi, Career of Agroindustrial Engineering, Latacunga Canton, Salache Parish, Salache Bajo Neighborhood, with the topic " Obtainment and characterization of the inulin from two agave varieties black cabuya (agave americana l.), and agave sisal (agave sisal p.), with three alcohol concentrations (40, 60, 80%), in the academic labs of the career of Agroindustrial Engineering from Technical University of Cotopaxi in the period 2015-2016 "….